ANALYSIS OF INTEREST AND PERFORMANCE OF EMPLOYEES AT LOCAL DRUG AND FOOD AGENCY IN MANADO - Cindhany Darmaria Faridhah Utami Mala; Ibnu Gholib Gandjar; Wakhid Slamet Ciptono (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Local Drug anf Food Agency in Manado (Balai Besar POM) is a Strategic Public Service Unit of National Drug and Food Agency (Badan POM) which expected capable to work effectively and efficiently to detects, prevents, and controls products, and also to protects consumer’s safety, security and health. Therefore, its necessary to know the current performance of quality control sector staff in Balai Besar POM Manado in order to increasing it. To detect staff performance of quality control sector in Balai Besar POM Manado which suitable to its importance level, and to detect the rank of performance variable which has biggest value on performance forming at Balai Besar POM Manado, its needs an approach using Importance‐Performance analysis of cartesius diagram to find out which organizational elements that most need improvement. This research is carried out on 34 quality control sector staff in Balai Besar POM Manado using descriptive research design and data collecting is obtained from primary and secondary data. Primary data is questionnares which distributed to quality control sector staff in Balai Besar POM Manado. Secondary data is comes from annual report of Balai Besar POM Manado. The results of this research based on Importance‐Performance analysis of cartesius diagram shows that ability to complete job and productivity variables has to get top priority from Balai Besar POM Manado to increase both variables, while ability to make decision and cooperation relationship with other people variables are also needs to increase, but these variables aren’t top priority. The order of performance variable rank based on its importance level is knowledge and understanding job, working attitude, productivity, ability to complete job, cooperation relationship with other people, and ability to make decision variables. Key Words : Balai Besar POM Manado, Performance, Importance‐Performance Analysis